Using Spatial Manipulation to Examine Interactions between Visual and Auditory Encoding of Pitch and Time - McLachlan, Neil M.; Greco, Loretta J.; Toner, Emily C.; Wilson, Sarah J. (Frontiers in Psychology, 2010)
Music notations use both symbolic and spatial representation systems. Novice musicians do not have the training to associate symbolic information with musical identities, such as chords or rhythmic and melodic patterns. They provide an opportunity to explore the mechanisms underpinning multimodal learning when spatial encoding strategies of feature dimensions might be expected to dominate. In this study, we applied a range of transformations (such as time reversal) to short melodies and rhythms and asked novice musicians to identify them with or without the aid of notation. Performance using a purely spatial (graphic) notation was contrasted with the more symbolic, traditional western notation over a series of weekly sessions. The results showed learning effects for both notation types, but performance improved more for graphic notation. This points to greater compatibility of auditory and visual neural codes for novice musicians when using spatial notation, suggesting that pitch and time may be spatially encoded in multimodal associative memory. The findings also point to new strategies for training novice musicians.